Effect of Statins on Insulin Requirements during Non-Cardiac Surgery. Issue 3 (May 2014) - Turan, A.; Egan, C.; You, J.; Sessler, D.; Abdelmalak, B.
Statins are thought to potentially impair glucose metabolism, increasing plasma glucose concentration. The effect of prolonged statin use on glucose metabolism among outpatients is thus well established. However, the impact of statin use on glucose concentrations and insulin requirements during surgery remains poorly characterised and may very well differ considering the substantial hyperglycaemic stress response to surgery. We conducted a study to test the hypothesis that patients taking statins preoperatively require more intraoperative insulin than non-users. We analysed 173 adults having major non-cardiac surgery who participated in the Dexamethasone, Light Anaesthesia and Tight Glucose Control Trial between 2007 and 2010. We compared statin and non-statin users on total amount of intraoperative insulin to maintain plasma glucose concentration within 4.4 to 6.1 mmol/l using the inverse propensity score weighting method. Sixty-seven patients were statin users and 106 were non-statin users. The estimated ratio of geometric means between the statin users and the non-users was 1.45 (95% confidence interval: 0.93, 2.26, statin versus non-statin, P =0.11). The total amount of intraoperative insulin usage did not differ significantly among patients taking different types of statins ( P =0.50). While the total amount of intraoperative insulin used was not statistically different between the statin users and non-users, we observed a potentially important trend toward insulin resistance intraoperatively among statin users during major non-cardiac surgery. This result is consistent with non-operative settings and cardiac surgery. Further investigation is essential to determine whether this effect is real and, if so, determine which specific statins are more associated with insulin resistance.